Anterior Chamber Angle and Anterior Chamber Volume in a 40- to 64-Year-Old Population. Issue 4 (July 2016) - Hashemi, Hassan; Khabazkhoob, Mehdi; Mohazzab-Torabi, Saman; Emamian, Mohammad Hassan; Shariati, Mohammad; Dadbin, Nooshin; Fotouhi, Akbar
Abstract : Purpose: To determine the distribution of the anterior chamber angle (ACA) and anterior chamber volume (ACV) in an Iranian population of 40- to 64-year-old people using the Pentacam. Methods: In this cross-sectional study, multistage sampling was used to select 300 clusters, including 6, 311 individuals from the city of Shahroud. All selected participants underwent examinations in one place. Optometric examinations, including measurement of visual acuity and refraction, and ophthalmologic examinations, including slit–lamp examination, were performed for all participants. Moreover, all patients underwent imaging with the Pentacam. Results: The mean ACA and ACV was 34.3° (95% confidence interval [CI]: 34.1°–34.5°) and 139 μL (95% CI: 137.7–140.3), respectively. In a multiple linear regression model, the ACA was inversely correlated with age (coefficient=−0.08), lens thickness (coefficient=−1.38), corneal diameter (coefficient=−0.36), and corneal curvature (coefficient=−1.43), and directly correlated with the anterior chamber depth (ACD) (coefficient=6.59). In another model, ACV was inversely correlated with age (coefficient=−0.37), central corneal thickness (coefficient=−0.04), and spherical equivalent (coefficient=−1.15), and directly correlated with the ACD (coefficient=85.67), lens thickness (coefficient=14.15), corneal diameter (coefficient=4.80), corneal curvature (coefficient=18.43), ACA (coefficient=0.65), and intraocular pressure (coefficient=0.23). Conclusion: The findings of this study could be used as a reference for diagnosis and treatment in Iran and the Middle East region. Increase in age and decrease in the ACD were important factors associated with decreased ACA and ACV, although the correlation of other biometric components was also evaluated. Some of these components, such as the corneal curvature and lens thickness, had a significant relationship with these two variables.